The rectifiable distance in the unitary Fredholm group - Andruchow, Esteban (2010)
Let Uc(H)={u:u unitary and u−1 compact} stand for the unitary Fredholm group. We prove the following convexity result. Denote by d∞ the rectifiable distance induced by the Finsler metric given by the operator norm in Uc(H). If u0,u1,u∈Uc(H) and the geodesic β joining u0 and u1 in Uc(H) satisfy d∞(u,β)<π/2, then the map f(s)=d∞(u,β(s)) is convex for s∈[0,1]. In particular, the convexity radius of the geodesic balls in Uc(H) is π/4. The same convexity property holds in the p-Schatten unitary groups Up(H)={u:u unitary and u−1 in the p-Schatten class} for p an even integer, p≥4 (in this case, the distance is strictly convex). The same results hold in the unitary group of a C∗-algebra with a faithful finite trace. We apply this convexity result to establish the existence of curves of minimal length with given initial conditions, in the unitary orbit of an operator, under the action of the Fredholm group. We characterize self-adjoint operators A such that this orbit is a submanifold (of the affine space A+K(H), where K(H)=compact operators).